Pemanfaatan Limbah Bonggol Jagung Menjadi Biobriket Dengan Proses Karbonasi Sebagai Energi Terbarukan - Chaliceta Fazanuari Islamia; Fairuz Zabaniyah; Yunita Anggraini; Nyko Joubu Soedjana; Denny Oktavina Radianto (KOLONI, 2024)
Biomass is a potential energy source and can be developed as an alternative energy source as a substitute for fossil fuels. Biomass can be converted into briquettes or charcoal which can be used as an energy source, such as for the drying process in processing crumb rubber and smoked sit. Biomass charcoal briquettes or biobriquettes are made from biomass charcoal, either in the form of parts that are intentionally used as raw material for briquettes or leftovers or waste from agro-industrial production/processing processes. For example, wood, coconut shells, palm shell charcoal, bamboo waste, corn cobs, rice husks and tobacco stem waste can be raw materials for biobriquettes. Apart from that, waste from the crumb rubber industry in the form of chips can also be used as biobriquettes. Biobriquette manufacturing technology is widely available. Making biobriquettes requires supporting materials such as clay, starch glue, water and other mixing materials. The composition of these materials really depends on the type of raw material for making biobriquettes. Before making biobriquettes, biomass must first be converted into charcoal, then the charcoal is crushed, mixed and molded into various briquette shapes such as cylinders, cubes and eggs. From several research results, in general the calorific value produced from biobriquettes is not significantly different compared to coal briquettes. Therefore, biobriquettes can be used as fuel for the natural rubber drying process.